A sagittal reference line using the preoperative radiograph in total knee arthroplasty - Hee-June Kim; Jeong-Woo Kim; Ji-Yeon Shin; Junekyu Kim; Hyun-Joo Lee; Kyeong-Hyeon Park; Hee-Soo Kyung (Journal of Orthopaedic Surgery, 2020)
Background: We evaluated the accuracy of a sagittal alignment of tibial component in total knee arthroplasty (TKA) with the sagittal reference line using the preoperative radiograph. Methods: We evaluated 151 patients who underwent primary TKA with posterior cruciate substituting type implant. For 75 patients, the sagittal reference line using preoperative radiograph (group A) was used, while for 76 patients the sagittal reference using intraoperative fibular shaft line (group B) was used. The parallel line (line S) to the anatomical axis of the tibia in the lateral plain radiograph was used as the sagittal reference. The distance from line S to proximal tibia cutting area and to skin surface 20 cm distal to the cutting area was measured in preoperative radiographs. Next, the distance to the extramedullary guide rod was applied intraoperatively, reflecting the results. The intraoperative fibular shaft line was determined using the connecting line between the tip of fibular head and the lateral malleolus. The postoperative tibial component slope angle and the difference to the target slope angle were compared. Results: The difference to the target angle was 1.8 ± 1.3° in group A, whereas the difference was 2.5 ± 1.4° in group B ( p = 0.04). The patients with difference within 3° to the target angle were 78.7% in group A and 61.8% in group B ( p = 0.024). Conclusion: The sagittal reference line using the preoperative lateral radiograph was helpful as a reference guide for the tibial slope in TKA.